Antitumor activity of Toluquinol - Torres-Vargas, José Antonio; Sounni, Nor Eddine; Medina-Torres, Miguel Ángel; Rodríguez-Quesada, Ana María; García-Caballero, Melissa (My University, 2022)
Colorectal cancer (CRC) is the third most common cause of cancer mortality worldwide, with more than 1.85 million cases and 850.000 deaths annually1. Currently, the primary methods for treating CRC are surgery, radiotherapy and chemotherapy, with targeted drugs playing an important role in the treatment of CRC. The most commonly used targeted drugs are directed against EGFR and VEGF2, but limitations have been observed with these drugs due to problems arising from drug resistance. Therefore, it is an urgent need to explore alternative signaling pathways and discover novel effective compounds2. In this context, it has been shown that the occurrence of CRC is linked to the PI3K/AKT/mTOR signaling pathway, one of the main drivers and regulators of tumor cell proliferation, growth, migration, survival and metabolism. Additionally, 60-70% of colon cancer patients show an activation of the AKT pathway and a reduction of PTEN expression levels2. Therefore, inhibitors of the PI3K/Akt/mTOR signaling have been suggested as potential therapeutic agents in the treatment of colorectal cancer1,2. Our continuing efforts to identify new anti-tumor drugs led us to focus on Toluquinol, a natural compound present in both fungi and plants, which has been previously characterized by us as an angiogenesis and lymphangiogenesis inhibitor3,4, as well as a compound displaying anti-inflammatory properties. In the present study, we have evaluated the anti-tumor effect of Toluquinol on a human colorectal cell line (HT29). Interestingly, we have observed that Toluquinol is able to modulate survival, proliferation, migration and apoptosis in HT29 cells, interfering with Akt/mTOR pathway. Altogether, out data suggests that Toluquinol is a promising drug candidate with potential for inhibiting colorectal cancer cell progression.
Keywords: Cáncer - Congresos; Toluquinol